Comparative Analysis of the Efficacy of Transcutaneous Electrical Nerve Stimulation in Somatic and Idiopathic Tinnitus Patients - Emre Soylemez; Aydin Sinan Apaydin; Zehra Aydoğan; Neslihan Hazal Şen; Murat Yasar; Ömer Gökay Argadal (Brain and Behavior)
ABSTRACT Objective This study aimed to investigate the effectiveness of transcutaneous electrical nerve stimulation (TENS) treatment in patients with chronic somatic tinnitus (CST) originating from the neck and idiopathic chronic subjective tinnitus (ICST). Methods The study was conducted on 21 CST and 25 ICST individuals. These individuals were divided into two groups. Active TENS therapy was applied to one group, and a placebo was applied to the other group. Tinnitus Handicap Inventory (THI), Visual Analog Scale (VAS), Beck Anxiety Inventory (BAI), and Short Form‐36 (SF‐36) were applied to the individuals before and after the therapy. Results In the CST group that received active treatment, significant improvements were noted in THI, VAS‐tinnitus, VAS‐neck pain, and SF‐36 (energy and pain) after treatment (p < 0.05). In the ICST group that received active treatment, significant improvements were observed in tinnitus loudness, THI, tinnitus loudness, BAI, VAS‐Tinnitus, and SF‐36 (physical function, mental health, and physical role limitations) after treatment (p < 0.05). Conclusion Although cervical TENS therapy is considered to be a more effective treatment method for neck‐related CST patients, our placebo‐controlled comparative study demonstrates that cervical TENS can be effectively used to alleviate tinnitus and improve the quality of life in both CST and ICST patients.